2018
DOI: 10.1021/acsami.7b18105
|View full text |Cite
|
Sign up to set email alerts
|

Cathodic Corrosion of a Bulk Wire to Nonaggregated Functional Nanocrystals and Nanoalloys

Abstract: A key enabling step in leveraging the properties of nanoparticles (NPs) is to explore new, simple, controllable, and scalable nanotechnologies for their syntheses. Among “wet” methods, cathodic corrosion has been used to synthesize catalytic aggregates with some control over their size and preferential faceting. Here, we report on a modification of the cathodic corrosion method for producing a range of nonaggregated nanocrystals (Pt, Pd, Au, Ag, Cu, Rh, Ir, and Ni) and nanoalloys (Pt50Au50, Pd50Au50, and AgxAu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
37
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(43 citation statements)
references
References 51 publications
1
37
0
1
Order By: Relevance
“…However, the atomistic aspects of the structural transformation and the surface evolution during cathodic corrosion are still poorly understood. So far, experiments using polycrystalline wires ( 10 17 ) have shown that the corrosion is anisotropic, and the surface roughening generated by cathodic corrosion is more pronounced around grain boundaries ( 14 ). The extent of roughness may, therefore, vary depending on the crystallographic distribution ( 11 13 ), electrolyte properties ( 14 , 15 ), and the pretreatment of the electrode ( 13 ).…”
mentioning
confidence: 99%
“…However, the atomistic aspects of the structural transformation and the surface evolution during cathodic corrosion are still poorly understood. So far, experiments using polycrystalline wires ( 10 17 ) have shown that the corrosion is anisotropic, and the surface roughening generated by cathodic corrosion is more pronounced around grain boundaries ( 14 ). The extent of roughness may, therefore, vary depending on the crystallographic distribution ( 11 13 ), electrolyte properties ( 14 , 15 ), and the pretreatment of the electrode ( 13 ).…”
mentioning
confidence: 99%
“…The production of the Cu particles for the slurry electrode is carried out via the cathodic corrosion method, which is inspired from Koper et al 39,40 An automatized set-up for Cu corrosion is developed for a constant production. The motorized equipment drives a thin Cu wire (dia.…”
Section: Cu Particle Synthesismentioning
confidence: 99%
“…The such developed catalysts exhibit not only good activity in various catalytic and electrocatalytic processes, but also the ability to form platinum upon the application of the alternating pulse current to the Pt foil electrodes . Moreover, the information on the electrochemical methods of synthesis of Pd‐based catalysts, using electrochemical reduction of Pd ions from its salt solutions or decomposition of a Pd electrode in Pd nanoparticles at a high cathodic potential is scarce.…”
Section: Microstructural and Electrochemical Characteristics Of Pt/c mentioning
confidence: 99%